Early Intervention in Psychosis Treatment Components Utilization in Patients Aged Over 35 - Jagger, Grace; de la Fuente-Tomas, Lorena; Stochl, Jan; Allan, Sophie M; Clay, Felix; Kenedler, Lizzie; Treise, Cate; Perez, Jesus (Community mental health journal, 2020)
Early Intervention in Psychosis (EIP) services have been youth-focused since their inception. In England, recent National Institute for Health and Care Excellence (NICE) guidelines and new National Health Service (NHS) Standards for EIP recommend the expansion of the age acceptability criterion from 14-35 to 14-65. In the Cambridgeshire and Peterborough EIP service (CAMEO), we ran a service evaluation to assess the initial impact of this policy change. It aimed to elicit EIP treatment components utilization by patients with first-episode psychosis (FEP) aged over 35, in comparison with those under 35. We found that the over-35s required more contacts from EIP healthcare professionals, especially from care coordinators (coefficient = .239; Robust SE = .102; Z = 6.42; p = 0.019) and social workers (coefficient = 18.462; Robust SE = .692; Z = .016; p < 0.001). These findings indicate that FEP patients aged over 35 may present with more complex and sustained clinical/social needs. This may have implications for EIP service development and commissioning.
Keywords: Over-35s; Psychosis; Service use; služby péče o duševní zdraví; Anglie; Adolescent; státní lékařství; Mental Health Services; State Medicine; lidé; Early intervention; psychotické poruchy; časná lékařská intervence; Age inclusivity; Aged; Early Medical Intervention; England; Psychotic Disorders; senioři; mladiství; Humans